Additive manufacturing extrusion device and forming method based on heat-force synergistic densification enhancement

By introducing thermal-force synergistic density enhancement technology of electric heating rollers and springs into the additive manufacturing extrusion device, the problem of insufficient component strength and corrosion resistance in traditional technology in extreme environments is solved, and high-density and high-strength component molding is achieved.

CN119795325APending Publication Date: 2025-04-11HEBEI UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510031054.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional extrusion additive manufacturing technology is difficult to meet the strength, durability and corrosion resistance requirements of components in extreme environments, limiting its application range.

Method used

An additive manufacturing extrusion device based on thermal-force synergistic density enhancement, which includes an electric heating roller and a spring, improves the density and strength of the material through heating and rolling techniques.

Benefits of technology

It significantly improves the density and compressive strength of the components, meets application needs in various environments, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119795325A_ABST
    Figure CN119795325A_ABST
Patent Text Reader

Abstract

The additive manufacturing extrusion device comprises a feeding hopper, a charging barrel, an auger, a nozzle, an electric heating roll shaft and a spring, the auger is installed on the upper portion in the charging barrel, two baffles are obliquely installed in the charging barrel space below the auger, and the two baffles are symmetrically arranged with the auger as the center; a first gap is formed between the two baffles, the baffles do not make contact with the packing auger, and the first gap is located under the packing auger; electric heating rollers are connected between the bottom of the charging barrel and the baffles through springs, the lower portions of the two baffles are each provided with one electric heating roller, a second gap is formed between the two electric heating rollers, and the diameter of the second gap is smaller than that of the nozzle; the spring is used for adjusting the size of the second gap between the two electric heating rolling shafts, so that the nozzle can uniformly discharge materials at the set rotating speed of the electric heating rolling shafts; and in the extrusion process, the electric heating roller is used for heating and compacting the material. And the density and the strength of the component are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to an additive manufacturing extrusion device and a molding method based on thermal-mechanical synergistic densification enhancement. Background Art

[0002] With the continuous development of science and technology, additive manufacturing technology has been widely used in many fields. Its application in the field of architecture is particularly prominent. For example, it can print components with complex internal cavities and supporting structures, thereby improving the aesthetics and functionality of the building. It can also reduce the amount of materials used and processing procedures, saving manpower, resources and energy consumption.

[0003] However, traditional extrusion additive manufacturing technology has gradually exposed some limitations. For example, in extreme environments such as polar regions and deserts, where material performance is extremely high, or in industrial fields such as chemical and metallurgy that are often in harsh environments with strong corrosion. Products made with traditional extrusion additive manufacturing technology often fail to meet the requirements in terms of strength, durability and corrosion resistance, limiting its application in these extremely harsh environments. Components manufactured with traditional 3D printing technology are difficult to meet the application requirements under these conditions, prompting people to seek a high-strength, high-density additive manufacturing material and technology.

[0004] In summary, in order to overcome the limitations of traditional extrusion-based additive manufacturing technology, improve the strength, durability and corrosion resistance of components, extend the service life of components and reduce maintenance costs, the present invention provides an additive manufacturing extrusion device based on thermal-mechanical synergistic densification enhancement and a molding method thereof. Summary of the invention

[0005] The purpose of the present invention is to provide an additive manufacturing extrusion device and a molding method thereof based on thermal-mechanical synergistic densification enhancement. The material properties obtained by the molding method are excellent, the density and strength of the product components are improved, and the application requirements in various environments are met.

[0006] To achieve the above object, the present invention proposes the following technical solutions:

[0007] In a first aspect, the present invention provides an additive manufacturing extrusion device based on thermal-mechanical synergistic densification enhancement, comprising a feed hopper, a barrel, an auger and a nozzle, the extrusion device further comprising an electric heating roller and a spring, an auger is installed in the upper part of the barrel, two baffles are obliquely installed in the barrel space below the auger, the two baffles are symmetrically arranged with the auger as the center, a first gap is provided between the two baffles, and the baffles do not contact the auger, and the first gap is located directly below the auger;

[0008] An electric heating roller is connected between the bottom of the barrel and the baffle plate through a spring, an electric heating roller is installed under each of the two baffle plates, and a second gap is provided between the two electric heating rollers, and the second gap is smaller than the nozzle diameter;

[0009] The spring is used to adjust the size of the second gap between the two electric heating rollers so as to ensure that the nozzle can discharge the material evenly at the set rotation speed of the electric heating rollers;

[0010] During the extrusion process, the heated rollers perform both heating and compacting on the material.

[0011] Furthermore, the electric heating roller is driven by a motor installed outside the barrel; the barrel has a diameter of 30-50 cm, the first gap is a long strip-shaped feeding hole, and the rotation speed of the electric heating roller is 300-400 r / min;

[0012] It is ensured that the slurry can be discharged evenly after reaching the nozzle through the long strip discharge hole and the second gap; the diameter of the nozzle is 15-30mm.

[0013] Furthermore, the electric heating roller contains a nickel-chromium alloy resistance wire with a diameter of 0.5 to 3 mm; the spring wire diameter of the spring is 3 mm, the outer diameter of the spring is 50 to 60 mm, the inner diameter of the spring is 44 to 54 mm, the spring stiffness is 280 to 500 N / m, the fatigue life is 80,000 to 100,000 times, and it is connected to the electric heating roller to give the electric heating roller pressure for rolling the material.

[0014] Furthermore, the feed hopper is connected to the inside of the barrel for injecting slurry materials; the auger is driven by a motor and is equipped with a limit switch and an emergency stop structure for conveying the slurry material to the nozzle.

[0015] In a second aspect, the present invention provides an additive manufacturing extrusion molding method based on thermal-mechanical synergistic densification enhancement, wherein the molding method uses the device described above and comprises the following steps:

[0016] A. Weigh the raw materials according to the mass fractions: 50-70 parts of cast stone clinker powder, 10-20 parts of polyurethane acrylic resin, 13.8 parts of light-burned magnesium oxide, 10.6 parts of magnesium chloride hexahydrate, 1.4 parts of silica fume, 0.2 parts of basalt fiber, and 12-16 parts of water;

[0017] B. mixing the magnesium chloride hexahydrate with water to obtain a magnesium chloride solution;

[0018] C. Pour the cast stone clinker powder, light-burned magnesium oxide, silica fume and basalt fiber into a powder mixer and mix them evenly to obtain a dry powder mixture;

[0019] D. Mixing the magnesium chloride solution, the dry powder mixture and the polyurethane acrylic resin and stirring them uniformly to obtain a slurry for additive manufacturing;

[0020] E. Adjust the second gap between the two electric heating rollers by the spring, set the speed of the electric heating rollers, transfer the obtained slurry to the pump barrel of the extrusion type 3D printer, and feed the barrel through the feed pipe through the feed funnel to test whether the nozzle discharges uniformly. After the nozzle discharges uniformly, start printing the sample;

[0021] F. After printing is completed, it is irradiated under ultraviolet light for 1.5-2.5 hours and air-cured at room temperature to obtain a component with good density and strength.

[0022] Furthermore, the compressive strength of the component is not less than 30 MPa, and the density is controlled above 2.34.

[0023] In the third aspect, the present invention also protects an additive manufacturing extrusion material with high density and strength, the raw materials of which include the following components in parts by mass: 50 to 70 parts of cast stone clinker powder, 0 to 20 parts of polyurethane acrylic resin, 13.8 to 18.4 parts of light-burned magnesium oxide, 10.6 to 16 parts of magnesium chloride hexahydrate, 1.4 parts of silica fume, 0.2 parts of basalt fiber, and 12 to 16 parts of water.

[0024] Furthermore, the cast stone clinker powder is waste from a cast stone production plant and has a density of 2.97 g / cm 3 , with a particle size of 0.125 mm, and the main components are 40.5% silicon dioxide, 17.8% iron oxide, 12.8% calcium oxide, 12.1% aluminum oxide, and a small amount of other oxides such as magnesium oxide, potassium oxide and titanium dioxide;

[0025] The viscosity of the polyurethane acrylic resin is 8000-12000cps;

[0026] The light-burned magnesium oxide has a purity of 90% and is an industrial-grade high-purity light magnesium oxide. Its ignition loss at 850°C is 3.21% and its bulk density is 0.25 g / cm 3 ;

[0027] The magnesium chloride hexahydrate has a magnesium chloride content greater than 98% and is in the form of flaky or granular colorless crystals;

[0028] The mass contents of the substances in the silica ash are: SiO2 content 84.49%, Fe2O3 content 6.63%, K2O content 2.45%, MgO content 1.54%, CaO content 1.04%, Na2O content 1.03%;

[0029] The basalt fiber has a length of 2 mm, a single fiber diameter of 6.23 μm, a breaking strength of 1937 MPa, an elastic modulus of 79, a breaking elongation of 2.9%, and a density of 2.6 g / cm 3 .

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The present invention uses magnesium-based gelling material (referring to the total amount of magnesium oxide and magnesium chloride hexahydrate) and polyurethane acrylic resin to provide the main mechanical strength, and the total amount does not exceed 30%, which greatly reduces the production cost.

[0032] 2. The material formula of the present invention selects cast stone clinker powder as the base material, and adds polyurethane acrylic resin combined with magnesium-based gelling material. The components can work synergistically, significantly improving the wear resistance of the material in a high-wear environment, and at the same time having good mechanical properties, can withstand large mechanical stress, and effectively improve the chemical corrosion resistance of the material. In addition, it also has the characteristics of light curing, can be quickly cured by ultraviolet rays, and is convenient for rapid molding after extrusion, and the cured film has excellent flexibility and high elongation at break.

[0033] 3. Compared with the traditional extrusion-type additive manufacturing device, the device of the present invention adds two electric heating rollers in the barrel and fixes them in the barrel near the nozzle through the baffle and spring. When the slurry is transported to the electric heating rollers through the auger, the slurry will absorb the heat from the rollers and evaporate some free water to improve the strength of the material. When the slurry is transported to the electric heating roller, a force will be applied to the electric heating roller. At this time, a slight deformation will occur at the spring to generate a reaction force, and the slurry will be squeezed by the electric heating roller to improve the strength of the material. At the same time, the density of the material is further improved through rolling, which helps to improve the wear resistance and chemical corrosion resistance of the material.

[0034] 4. The device of the present invention can realize uniform extrusion of materials and perform thermal-mechanical synergistic densification enhancement on the materials. It has a simple structure and is easy to operate and clean. The molding method can prepare additive manufacturing components with good strength, wear resistance and chemical corrosion resistance at a low cementitious material dosage. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 A schematic diagram of the structure of an additive manufacturing extrusion device based on thermal-mechanical synergistic densification enhancement according to an embodiment;

[0036] Among them: 101-motor, 102-auger, 103-first baffle, 104-second baffle, 105-first spring, 106-second spring, 107-first electric heating roller, 108-second electric heating roller, 109-nozzle, 110-barrel, 111-feeding funnel. DETAILED DESCRIPTION

[0037] In order to make the technical purpose, technical solution and beneficial effects of the present invention clearer, the material and molding method of the present invention are further described below in conjunction with the accompanying drawings and specific embodiments.

[0038] The invention is based on the heat-mechanical synergistic densification enhanced additive manufacturing extrusion device (see Figure 1 ), including a feed hopper 111, a barrel 110, an auger 102, an electric heating roller and a spring.

[0039] The feeding funnel is communicated with the interior of the barrel.

[0040] The auger is driven by a motor and is equipped with a limit switch and an emergency stop structure, and is used to transport the slurry material to the nozzle.

[0041] The first baffle 103 and the second baffle 104 have the same structure, and both are arranged symmetrically and tilted toward the center. The baffle is fixedly connected to the barrel wall, and the end of the baffle (the end close to the auger) is in the shape of an arc circumscribed to the electric heating roller. The baffle is first used to guide the slurry so that the slurry can be easily transported to the electric heating roller. Secondly, it plays a limiting role on the electric heating roller so that the spring connected to the electric heating roller can have a certain amount of compression in the initial state. Finally, the baffle can be used to clean the surface slurry of the electric heating roller. The baffle is tangent to the electric heating roller. When the electric heating roller rotates, the baffle can scrape off the residual slurry on the electric heating roller.

[0042] The first electric heating roller 107 and the second electric heating roller 108 are arranged symmetrically relative to the axis of the auger. The two have the same structure and are respectively connected to the first spring 105 and the second spring 106. The electric heating rollers are driven by a motor and contain a nickel-chromium alloy resistance wire with a diameter of 0.5 to 3 mm for heating and compacting the material.

[0043] The spring wire diameter of the spring is 3mm, the outer diameter of the spring is 50-60mm, the inner diameter of the spring is 44-54mm, the spring stiffness is 280-500N / m, the fatigue life is 80000-100000 times, and it is connected to the electric heating roller to give the electric heating roller pressure for rolling the material.

[0044] In the initial stage of the device installation, the compressed length of the spring or the length of the spring in the natural state can be adjusted according to the actual working conditions, and then the size of the second gap between the two electric heating rollers can be adjusted to adapt to different working requirements. The size of the second gap shall not be greater than the inner diameter of the nozzle. When the device is installed, the size of the second gap cannot generally be changed. The size of the second gap is defined as the shortest distance between the outer circumferences of the two electric heating rollers.

[0045] Example 1

[0046] The raw materials were weighed according to their mass proportions: 70 parts of cast stone powder clinker, 10 parts of polyurethane acrylic resin, 13.8 parts of light-burned magnesium oxide, 10.6 parts of magnesium chloride hexahydrate, 1.4 parts of silica fume, 0.2 parts of basalt fiber, and 14 parts of water.

[0047] The cast stone powder clinker is a light grey powder from the waste of cast stone production plant. The density is 2.97g / cm 3 The particle size is 0.125mm. The main components are 40.5% silicon dioxide, 17.8% iron oxide, 12.8% calcium oxide, 12.1% aluminum oxide, and a small amount of other oxides such as magnesium oxide, potassium oxide and titanium dioxide.

[0048] The viscosity of the polyurethane acrylic resin is 8000 cps.

[0049] The light-burned magnesium oxide has a purity of 90% and is an industrial-grade high-purity light magnesium oxide. It is a light yellow powder solid with a loss on ignition (850°C) of 3.21% and a bulk density of 0.25 g / cm 3 .

[0050] The magnesium chloride hexahydrate has a magnesium chloride content of more than 98% and is in the form of flaky or granular colorless crystals.

[0051] The silica ash contains 84.49% SiO2, 6.63% Fe2O3, 2.45% K2O, 1.54% MgO, 1.04% CaO and 1.03% Na2O.

[0052] The basalt fiber has a length of 2 mm, a single fiber diameter of 6.23 μm, a breaking strength of 1937 MPa, an elastic modulus of 79, a breaking elongation of 2.9%, and a density of 2.6 g / cm 3 .

[0053] Dissolving magnesium chloride hexahydrate in water to prepare a magnesium chloride solution;

[0054] Pour the cast stone clinker powder, light-burned magnesia, silica fume and basalt fiber into a mixer and mix for 5 minutes to obtain a uniform dry powder mixture;

[0055] The magnesium chloride solution, the dry powder mixture and the polyamino acrylic resin were mixed and stirred for 5 minutes to obtain an additive manufacturing slurry material;

[0056] The obtained slurry is transferred to the 3D printer feed hopper 109 and the printing of the sample is started.

[0057] After the slurry enters from the feed funnel, it is transported by the auger 102 to the electric heating rollers (107 and 108) containing 0.5 mm resistance wire and connected to the spring, heated by the electric heating rollers 107 and 108, and extruded from the nozzle 109 after rolling.

[0058] The auger has a spiral diameter of 200 mm, a spiral length of 400 mm, and a rotation speed of 50 r / min.

[0059] The electric heating roller has a diameter of 70 mm, a rotation speed of 300 r / min, an internal resistance wire diameter of 0.5 mm, a resistivity of 1.13±0.05 μΩ·m (20°C), a rated power of 1200 w, and a maximum operating temperature of 1200°C.

[0060] The spring wire diameter of the spring is 3mm, the outer diameter of the spring is 50mm, the inner diameter of the spring is 44mm, the spring stiffness is 500N / m, the fatigue life is 80000-100000 times, and it is connected to the electric heating roller to apply pressure to the electric heating roller for rolling the material.

[0061] The nozzle diameter is 20 mm and the nozzle length is 50 mm.

[0062] After printing, it was irradiated under ultraviolet light for 2 hours and air-cured at room temperature until 28 days old to obtain a printed sample. The printed test block was cut to obtain a standard test piece, and the density and compressive strength were tested and compared with the traditional C30 concrete test block. The concrete compressive strength test of this embodiment was measured in accordance with GB-T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The results show that compared with traditional concrete, this embodiment can prepare components with good density and strength at a lower cementitious material.

[0063] Example 2

[0064] The difference between this embodiment and embodiment 1 is that the electric heating roller containing 0.5mm resistance wire is replaced with an electric heating roller containing 3mm resistance wire. The thinner the resistance wire, the greater the resistance, and the more heat can be generated. The obtained printed test block is cut to obtain a standard test piece, and the density and compressive strength tests are carried out and compared with the traditional C30 concrete test block. The concrete compressive strength test of this embodiment is measured in accordance with GB-T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The results show that compared with traditional concrete, this embodiment can prepare components with good density and strength at a lower cementitious material.

[0065] Example 3

[0066] The difference between this embodiment and Example 1 is that 10 parts of polyurethane acrylic resin in the material ratio are removed, 13.8 parts of light-burned magnesium oxide are replaced with 18.4 parts of light-burned magnesium oxide, and 10.6 parts of magnesium chloride hexahydrate are replaced with 16 parts. The obtained printed test block is cut to obtain a standard test piece, and the density and compressive strength are measured and compared with the traditional C30 concrete test block. This comparative example is measured according to the concrete compressive strength test in accordance with GB-T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The results show that in the absence of polyurethane acrylic resin, the setting time of the material in this embodiment is relatively long, and the initial setting time is about 7h (the initial setting time in Example 1 is controlled at about 2h), which is time-consuming and relatively increases the construction cost. In addition, the compressive strength at this time is relatively poor, less than 30MPa. However, this embodiment still has an advantage in density at a lower proportion of cementitious materials.

[0067] Example 4

[0068] The difference between this embodiment and Example 1 is that a traditional extrusion-type additive manufacturing nozzle (that is, no electric heating roller works under the same conditions) is used for printing. The obtained printed test block is cut to obtain a standard test piece, and the density and compressive strength tests are carried out, and compared with the traditional C30 concrete test block. This embodiment is measured according to the concrete compressive strength test in accordance with GB-T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The results show that the setting time of the traditional extrusion-type additive manufacturing nozzle used in this embodiment is slower, but the formed test block still has an advantage in density over traditional concrete.

[0069] The specific test results of Examples 1-4 are shown in Table 1.

[0070] Table 1

[0071] type Compressive strength(MPa) <![CDATA[Density (g / cm 3 )]]> Traditional concrete 32.4 2.34 Example 1 35.5 2.43 Example 2 33.3 2.38 Example 3 28.6 2.46 Example 4 30.4 2.39

[0072] It can be seen from the above table that the compressive strength of the component of the present invention is controlled at about 30MPa (28.6-35.5MPa), and the density is greater than 2.34g / cm 3 Its excellent density and compressive strength can extend the service life of the component and make it reliable for a long time. In particular, the heat-mechanical synergistic densification and reinforcement extrusion molding method of the present application is selected, and its strength and density are both optimal, and the density and compressive strength of the component are not lower than C30 concrete.

[0073] The above descriptions are only several embodiments of the present invention, and are intended to better explain the materials, devices and molding methods of the present invention, but are not intended to limit the scope of the present invention. Any simple modification, parameter changes, etc. of the present invention are within the scope of the technical solution of the present invention.

[0074] Any matters not described in the present invention are applicable to the prior art.

Claims

1. An additive manufacturing extrusion device based on thermal-mechanical synergistic densification enhancement, comprising a feed hopper, a barrel, an auger and a nozzle, characterized in that: The extrusion device also includes an electric heating roller and a spring. An auger is installed in the upper part of the barrel. Two baffles are obliquely installed in the barrel space below the auger. The two baffles are symmetrically arranged with the auger as the center. There is a first gap between the two baffles, and the baffles do not contact the auger. The first gap is located directly below the auger. An electric heating roller is connected between the bottom of the barrel and the baffle plate through a spring, an electric heating roller is installed under each of the two baffle plates, and a second gap is provided between the two electric heating rollers, and the second gap is smaller than the nozzle diameter; The spring is used to adjust the size of the second gap between the two electric heating rollers so as to ensure that the nozzle can discharge the material evenly at the set rotation speed of the electric heating rollers; During the extrusion process, the heated rollers perform both heating and compacting on the material.

2. The device according to claim 1, characterized in that The electric heating roller is driven by a motor installed outside the barrel; the barrel has a diameter of 30-50cm, the first gap is a long strip-shaped discharge hole, and the rotation speed of the electric heating roller is 300-400r / min; it is ensured that the slurry can be discharged evenly after passing through the long strip-shaped discharge hole and the second gap to reach the nozzle; the nozzle has a diameter of 15-30mm.

3. The device according to claim 1, characterized in that The electric heating roller contains a nickel-chromium alloy resistance wire with a diameter of 0.5 to 3 mm; the spring wire diameter of the spring is 3 mm, the spring outer diameter is 50 to 60 mm, the spring inner diameter is 44 to 54 mm, the spring stiffness is 280 to 500 N / m, and the fatigue life is 80,000 to 100,000 times. It is connected to the electric heating roller to give the electric heating roller pressure for rolling the material.

4. The device according to claim 1, characterized in that The feed hopper is connected to the inside of the barrel and is used for injecting slurry materials; the auger is driven by a motor and is equipped with a limit switch and an emergency stop structure, and is used for conveying the slurry materials to the nozzle.

5. An additive manufacturing extrusion molding method based on thermal-mechanical synergistic densification enhancement, characterized in that: The molding method uses the device described in any one of claims 1 to 4, comprising the following steps: A. Weigh the raw materials according to the mass fractions: 50-70 parts of cast stone clinker powder, 10-20 parts of polyurethane acrylic resin, 13.8 parts of light-burned magnesium oxide, 10.6 parts of magnesium chloride hexahydrate, 1.4 parts of silica fume, 0.2 parts of basalt fiber, and 12-16 parts of water; B. mixing the magnesium chloride hexahydrate with water to obtain a magnesium chloride solution; C. Pour the cast stone clinker powder, light-burned magnesium oxide, silica fume and basalt fiber into a powder mixer and mix them evenly to obtain a dry powder mixture; D. Mixing the magnesium chloride solution, the dry powder mixture and the polyurethane acrylic resin and stirring them uniformly to obtain a slurry for additive manufacturing; E. Adjust the second gap between the two electric heating rollers by the spring, set the speed of the electric heating rollers, transfer the obtained slurry to the pump barrel of the extrusion type 3D printer, and feed the barrel through the feed pipe through the feed funnel to test whether the nozzle discharges uniformly. After the nozzle discharges uniformly, start printing the sample; F. After printing is completed, it is irradiated under ultraviolet light for 1.5-2.5 hours and air-cured at room temperature to obtain a component with good density and strength.

6. The molding method according to claim 5, characterized in that: The compressive strength of the component is not less than 30MPa, and the density is controlled above 2.

34.

7. An additive manufacturing extrusion material having high density and strength, characterized in that: The raw materials of the material include the following components in parts by mass: 50-70 parts of cast stone clinker powder, 0-20 parts of polyurethane acrylic resin, 13.8-18.4 parts of light-burned magnesium oxide, 10.6-16 parts of magnesium chloride hexahydrate, 1.4 parts of silica fume, 0.2 parts of basalt fiber, and 12-16 parts of water.

8. The material according to claim 7, characterized in that: The cast stone clinker powder comes from the waste of the cast stone production plant, and its density is 2.97g / cm 3 , with a particle size of 0.125 mm, and the main components are 40.5% silicon dioxide, 17.8% iron oxide, 12.8% calcium oxide, 12.1% aluminum oxide, and a small amount of other oxides such as magnesium oxide, potassium oxide and titanium dioxide; The viscosity of the polyurethane acrylic resin is 8000-12000cps; The light-burned magnesium oxide has a purity of 90% and is an industrial-grade high-purity light magnesium oxide. Its ignition loss at 850°C is 3.21% and its bulk density is 0.25 g / cm 3 ; The magnesium chloride hexahydrate has a magnesium chloride content greater than 98% and is in the form of flaky or granular colorless crystals; The mass contents of the substances in the silica ash are: SiO2 content 84.49%, Fe2O3 content 6.63%, K2O content 2.45%, MgO content 1.54%, CaO content 1.04%, Na2O content 1.03%; The basalt fiber has a length of 2 mm, a single fiber diameter of 6.23 μm, a breaking strength of 1937 MPa, an elastic modulus of 79, a breaking elongation of 2.9%, and a density of 2.6 g / cm 3 .

Citation Information

Cited By

  • Continuous fiber 3D printing nozzle structure and composite material product

    CN121043403A

  • Continuous fiber 3D printing nozzle structure and composite product

    CN121043403B